Análisis comparativo de herramientas de integración continua: caso de estudio Jenkins vs Travis - Farinango Alcásiga, Paola Elizabeth (2022)
The actual research project was made with aim at describing, through a documentary and practical comparative analysis, the Continuous Integration tools effectiveness for recommending their application into software development projects. It was research methodologies different types, such as, qualitative research, which it helped to assess the continuous integration tools characteristics, descriptive research that allowed emphasizing the study object, which are the Jenkins and Travis tools, furthermore, it was used narrative research for describing the tools characteristics and determine, what is the best alternative for continuous integration process. For practical cases execution was used agile development approaches, such as, the code collective ownership, teamwork and Jenkins and Travis as key tools for the continuous integration; Github as a repository for the project code and for version control. This way, it was applied the Continuous Integration practical comparative process with a developed web system into Visual Studio Code with Python programming language. The project validation was made, through the expert judgment technique by using Cronbach's Alpha Coefficient with a 0.73 value, what is equivalent to a Good rating. Finally, it can be concluded, which the project aim was fulfilled, since the result is, a theoretical and practical comparative work, what it has been verified, what is the best Continuous Integration tool between the proposals, which are Jenkins and Travis, the proposal is most effective proposal Jenkins.